Daphne's Diary of Daily Disasters. The vampire dare! - Moss, Marissa (Simon & Schuster Books for Young Readers, 2011)
In her diary, fourth-grader Daphne Davis draws and writes about her attempt to stop classmates from thinking she has cooties after what she thought would be a "cool" vampire outfit makes her the laughingstock of costume day.